Fabricación de monocristales de Zr-Alfa - Nicolai, L. I.; Balart, Silvia Noemí; Varela, Nilda; de Tendler, R. H. (Comisión Nacional de Energía Atómica; Argentina, 1981)
Fil: Nicolai, L. I. Comisión Nacional de Energía Atómica; Argentina